(untitled) (Research, Society and Development, 2021)
Introduction: Temporomandibular disorders (TMD) - recognized as the most common chronic orofacial pain condition - significantly impacts individuals’ quality of life and social coexistence. Therefore, this study aimed to analyze the effects of low-level laser therapy (LLLT) on functional improvements in the temporomandibular joints (TMJ). Method: The research was carried out at the Universidade Federal do Piauí on 32 young adults with signs and symptoms of TMD, who were divided into the intervention group (IG) and the control group (CG). The IG was administered the LLLT application directly on the TMJ. While both groups were subjected to the same procedures, for the CG, the laser device was turned off. Results: The mean age of the participants was 21.87 ± 2.4 years, with a predominance of females (87.5%) over males (12.5%). Homogeneity was observed between the CG and IG concerning the presence of pain from palpation. The decrease in the pain of the musculature was relevant, with emphasis on the IG, which used LLLT. Moreover, there was an increase in participants, who rated on the pain scale their pain as “0” (no pain), and presented increased measures of joint mobility of the mandible and cervical spine, with relief of the painful symptoms, by breaking the pain-spasm-pain cycle. Conclusion: LLLT promotes a significant reduction of pain from palpation, improves the range of motion, and generates immediate and long-lasting benefits.